The Evolution of Emoji Language: Linguistik and Social Implications in Digital Communication - Ahmad Zuhdi; Fakhri Yusuf (Yayasan Adra Karima Hubbi, 2024)
Background. Emojis have become an important part of digital communication, being used extensively to express emotions and clarify the meaning of messages. Although their use continues to increase, there has not been much research on how emojis affect linguistics and social interaction, especially in relation to different cultural contexts. Purpose. This research aims to explore the evolution of emoji language and its impact on digital communication, as well as understand the differences in the use of emoji in various cultures and formal and informal situations. Method. This study uses a descriptive qualitative method by collecting data through questionnaires and in-depth interviews with 100 respondents who use social media. Text analysis was also carried out to identify patterns of emoji use in daily communication. Results. The results showed that emojis were more often used in informal conversations to convey positive emotions, while their use in formal contexts was more limited and cautious. There are significant differences in the use of emojis between Western and Asian cultures, with Western cultures more likely to use facial expression-based emojis and Asian cultures preferring neutral symbols. Conclusion. The study concluded that emojis serve as an effective visual communication tool, but their use is greatly influenced by social and cultural contexts. This study made a significant contribution to the understanding of visual language in digital communication and paved the way for further research on the use of emojis in professional and formal contexts.